Urgensi Pengaturan Kaderisasi Partai Politik pada Undang-Undang Nomor 2 Tahun 2011 dalam Sistem Hukum Nasional - Sandroin Labada; Agnes Fitiyantica (Decisio: Jurnal Ilmiah Hukum, 2026)
This study aims to analyze the regulation of political party cadreization under Law Number 2 of 2011 concerning Political Parties and to examine the urgency of strengthening such regulation within the framework of the national legal system in Indonesia. This research employs a normative juridical method using statutory and conceptual approaches. The data used consist of primary legal materials in the form of legislation and secondary materials such as books and scholarly journals. The findings indicate that the regulation of political party cadreization remains general and does not provide clear normative standards regarding cadreization systems, evaluation mechanisms, or the implementation of merit-based political recruitment. This condition potentially encourages pragmatic and elitist recruitment practices within political parties. Therefore, strengthening cadreization regulation through standardized political education, meritocratic systems, and transparent supervision mechanisms is necessary to support democratic consolidation and the development of the national legal system.